Peran Zakat Bagi Peningkatan Ekonomi Umat (Studi Kasus BPZIS Bank Mandiri Periode Januari-Juni 2014) - Muhammad Yusuf (STID DI AL-HIKMAH, 2016)
Allah obliges give charity for his people to clean up the property. In addition to this, the charity is worship that has a very important position and strategic to the economic development of the people. Zakat has a very important role in the eradication of poverty. Therefore, the role of zakat in the economic improvement of the people needs to be improved. In order for a role in the increase of the maximum, then the charity needs to be managed properly. Management of zakat must be performed by various parties with the aim of economic improvement of the people. One of the institutions playing an active role in the management of zakat is BPIZ Bank Mandiri. This article aims to determine the role of zakat for economic improvement BPIZ people managed by the Bank. The conclusion is BPZIS bank has played an active role in building the economy of the people, through a development program of science, economic development, social development and health and building infrastructure.